2020
DOI: 10.15835/nbha48312000
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic biofortification with selenium improves the yield and nutraceutical quality in tomato under soilless conditions

Abstract: Selenium (Se) is an essential element for humans. Its consumption comes from food of animal or vegetal origin; whose content varies widely depending on its availability in soil or anthropogenic sources. Biofortification improves food nutritional quality, and its consumption has a positive influence in human health. Thus, the objective of this research was to assess agricultural biofortification with Se in tomato fruit and its effects on yield, nutraceutical quality, and antioxidant capacity.  Five Se doses (0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
1
3
0
2
Order By: Relevance
“…The addition of 8 mg L -1 of Se decreased 12.5% the yield with respect to the treatment without the trace element (Table 1), on the other hand, it has been reported that high doses of Se decrease crop yield, because it acts as a lipid pro-oxidant and increases the production of free radicals causing oxidative stress (Zięba et al, 2020); however, at low doses, yield is improved (Zahedi, Hosseini, Meybodi, and da Silva, 2019;Rady, Belal, Gadallah, and Semida, 2020) species under conditions stress (Hasanuzzaman et al, 2020). Plant response to Se depends on its concentration; since at low doses yield is promoted and moderate doses improve the quality characteristics of fruit (Gaucin-Delgado et al, 2020); while high concentrations can cause toxicity and cell death (Gupta and Gupta, 2017).…”
Section: Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of 8 mg L -1 of Se decreased 12.5% the yield with respect to the treatment without the trace element (Table 1), on the other hand, it has been reported that high doses of Se decrease crop yield, because it acts as a lipid pro-oxidant and increases the production of free radicals causing oxidative stress (Zięba et al, 2020); however, at low doses, yield is improved (Zahedi, Hosseini, Meybodi, and da Silva, 2019;Rady, Belal, Gadallah, and Semida, 2020) species under conditions stress (Hasanuzzaman et al, 2020). Plant response to Se depends on its concentration; since at low doses yield is promoted and moderate doses improve the quality characteristics of fruit (Gaucin-Delgado et al, 2020); while high concentrations can cause toxicity and cell death (Gupta and Gupta, 2017).…”
Section: Yieldmentioning
confidence: 99%
“…One strategy to increase Se content in food is through biofortif ication consisting potentiate the bioactivity and Se content in the edible parts of plants (Gaucin-Delgado et al, 2020). Fertilization is the most practical way to introduce Se into the food supply chain through agronomic practices; biofortif ication has been done successfully in different cultures increasing food and nutrition security of individuals, families and general population (Schiavon and Pilon, 2017), following improved agronomic characteristics, increasing food production and content of phytochemicals (Hossain et al, 2021), which help address nutritional def iciencies that are present in human diet (Bocchini et al, 2018); allowing faster to reach poorest communities, which have no resources to buy nutritional supplements suitable for the recommended daily intake (Mikula et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The climate of study area is dry steppe; average temperature of 21 °C and annual rainfall of 253 mm. The soil texture is sandy loam (81 % sand, 14 % silt and 5 % clay); bulk density 1.67 g.cm -3 ; pH of 8.37; water retention capacity of 25.2 %; electrical conductivity of 1.28 dS.m -1 ; organic matter content 1.18 mg.kg -1 ; total nitrogen of 32.8 mg.kg -1 ; y el contenido antioxidante (Gaucín-Delgado et al, 2020) y su concentración en la parte comestible (Kuldeep et al, 2010). Unas de las formas de aplicar el Se a las plantas es mediante la aplicación de selenito de sodio (Na 2 SeO 3 ).…”
Section: Study Areaunclassified
“…Foliar fertilization to agricultural crops is an alternative for incorporating Se into the food chain. Although Se is not considered essential to plants, it has been shown that at low concentrations Se increases crop growth, yield and antioxidant content (Gaucín-Delgado et al, 2020) and its concentration in the edible part (Kuldeep et al, 2010). One of the ways of applying Se to plants is through application of peroxidasa, tiroxina 5-deiodinasa y selenoproteína.…”
Section: Introductionmentioning
confidence: 99%
“…El tomate (Solanum lycopersicum L.) es el vegetal más consumido y producido a nivel mundial, siendo un alimento funcional por el contenido de sustancias bioactivas que benef ician la salud humana (Andrade-Sifuentes et al, 2020), como lo son los antioxidantes, que reparan el daño celular, previenen el cáncer y el envejecimiento (Gaucín-Delgado et al, 2020). El mayor productor mundial es China con 125 700 000 Mg en el 2019 (FAOSTAT, 2022).…”
Section: Introductionunclassified